The Perceptions Of Adolescent Women On Early Marriage at SMA PAB 5 Klumpang, Deli Serdang in 2021 - Utary Dwi Listiarini; Indah Dewi Sari; Ani Deswita Chaniago (International Archives of Medical Sciences and Public Health, 2022)
Objective: Early marriage is a marriage vow in the eyes of religion and law carried out by couples who are underage and under the reproductive age threshold, which is less than 20 years for women and less than 25 years for men. Objective : To determine the perception of young women about early marriage at SMA PAB 5 Klumpang Deli Serdang in 2021. Methods : Using this type of research is an analytical survey with a cross sectional approach. The location of this research was carried out at PAB 5 High School from August to November 2021. The population was 31 young women who were less than 20 years old and the sample was taken from the entire population. Results: Shows that the perception of adolescents on the cognitive aspect of early marriage using the chi square test results has a p value of 0.002, the adolescent's perception of the affective aspect of early marriage using chi square has a p value of 0.005, and the cognitive adolescent perception of early marriage using the test chi square has a p value of 0.004, so that there is a significant relationship between adolescent perceptions of early marriage at SMA PAB 5 Deli Serdang. Conclusion: There is a teenage perception about early marriage at SMA PAB 5 Deli Serdang in 2021. The researcher gives advice to the principal to cooperate with the puskesmas in terms of providing information about early marriage that is closely related to women's physical and reproductive health.chieve success in carrying out Early Initiation of Breastfeeding (IMD).